Some dilemmas regarding implementation of the Law on Prevention of Domestic Violence - Kolarić Dragana; Marković Saša (Anali Pravnog Fakulteta u Beogradu)
The paper contains an analysis of certain provisions of the Law on the Prevention of Domestic Violence and the first effects of its implementation. At the very beginning the question is asked of justification of the Law on the Prevention of Domestic Violence. Almost on a daily basis nowadays the news headlines refer to violence among the family members, particularly the violence of men against women and children. The main debate in media is about whether the state organs and society as a whole have taken all necessary steps to prevent violence from happening at all. The authors point to the unacceptable terminology of the legislator. There are many questions asked and an attempt is made to give the answers to some of them following the legal norms. Who is the possible perpetrator of domestic violence? What kind of procedure are we talking about? What is the role of the defender in this procedure? Do urgent measures play preventive or repressive role? Has their imposing become a dominant manner in preventing and suppressing domestic violence? Has the right to freedom of a possible perpetrator been jeopardized? What are the first effects of such manner of conduct of state organs, primarily the police, the public prosecution office and the court? How can possible abuses be prevented? One of the effects of the implementation of the Law on the Prevention of Domestic Violence should be prevention - the reduction in number of criminal offences of domestic violence. However, analyzing the available data the authors have come to quite the opposite conclusions. This means that the state has not responded in the best manner, using strict scientific reasoning and objective approach, to the matter of doctrinal analysis, and this is the problem of domestic violence.